Safety, pharmacokinetics and dose-response characteristics of GSK2269557, an inhaled PI3Kδ inhibitor under development for the treatment of COPD. (October 2017) - Cahn, A.; Hamblin, J.N.; Begg, M.; Wilson, R.; Dunsire, L.; Sriskantharajah, S.; Montembault, M.; Leemereise, C.N.; Galinanes-Garcia, L.; Watz, H.; Kirsten, A.M.; Fuhr, R.; et al.
Abstract: Background: While current therapies reduce symptoms in chronic obstructive pulmonary disease (COPD) patients, substantial unmet need remains and novel treatments are highly desired. Phosphoinositide 3-kinase δ (PI3Kδ) is a lipid kinase specifically expressed in leucocytes and involved in their recruitment and activation. This study evaluated the safety, pharmacokinetics (PK) and dose-response characteristics of inhaled GSK2269557, a PI3Kδ inhibitor, in moderate-to-severe COPD patients with stable disease. Methods: In this randomised, double-blind, placebo controlled, parallel group study, patients received once daily inhaled treatment with GSK2269557 1000 μg or placebo for 14 days (Part A, primary aim safety, N = 28 patients). In part B of the study (primary aim pharmacodynamic dose-response, N = 36 patients), GSK2269557 100, 200, 500, 700, 1000, 2000 μg or placebo was given for 14 days. In both Part A and B, GSK2269557 was added to the usual maintenance therapy. Safety, PK assessments and induced sputum collection for cytokine analysis were conducted at baseline and after 7 and 14 days of treatment. Adverse events (AEs) were monitored throughout. Results: In Part A, mean age was 61.7 years (SD 6.7), 29% were females, and mean FEV1 % predicted was 59.7% (SD 11.4) 2 . In Part B, mean age was 63.3 years (SD 6.3), 44% were females, and mean FEV1 % predicted was 56.5% (SD 11.5) 2 . GSK2269557 was well tolerated in both parts of the study; the most commonly reported AEs were cough and headache, with cough being reported with a greater incidence in the GSK2269557 groups vs. placebo (Part A: 19% vs. 14% and Part B: range of 0–80% for different doses vs. 0% on placebo). No drug-related serious AEs or clinically significant changes in any other safety parameters were reported. GSK2269557 was rapidly absorbed into plasma following all doses with a maximum peak at approximately 2 h. Following repeat administration, accumulation in plasma was approximately 2–3 fold from Day 1 to Day 7. At Day 14, relative to placebo, sputum interleukin (IL)-8 and IL-6 levels were reduced on average by 32% and 29% respectively after inhalation of GSK2269557 1000 μg in Part A. In Part B, although inhibition of both IL-8 and IL-6 levels was observed, the levels were variable and there was insufficient evidence to support a monotonic dose-response. Conclusions: In this study, inhaled GSK2269557 had an acceptable safety profile for progression into larger studies in COPD patients. Moreover, inhalation of GSK2269557 resulted in suppression of sputum IL-8 and IL-6 levels, consistent with the known anti-inflammatory activity of a PI3Kδ inhibitor. Inhibition of inflammatory cytokines in the airway compartment may contribute to the potential therapeutic benefit of a PI3Kδ inhibitor in chronically inflamed COPD patients.